2022
DOI: 10.1155/2022/3079823
|View full text |Cite
|
Sign up to set email alerts
|

Deoxyschizandrin Inhibits the Proliferation, Migration, and Invasion of Bladder Cancer Cells through ALOX5 Regulating PI3K-AKT Signaling Pathway

Abstract: Objective. Deoxyschizandrin has a significant inhibitory effect on a variety of tumor cells. However, the effect of Deoxyschizandrin on bladder cancer cells and its mechanism are still unclear. Methods. Bladder cancer cells were treated with different concentrations of Deoxyschizandrin for 24 h, 48 h, and 72 h. The inhibition rate of cell proliferation was detected by CCK-8 assay. The changes of cell migration and invasion were detected by wound healing and Transwell assay. Based on the structure of Deoxyschiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Indeed, our results provide evidence for a more intensive autophagy present in cells treated with 2. A novel study of Chi et al indicates that the downregulation of 5-Lipoxygenase via the PI3K/Akt signaling pathway results in the reduced proliferation and migration of tumor cells, confirming, once again, the importance of this enzyme in tumor treatment [43]. Nevertheless, one should have in mind that the inhibition of solely 5-LO could result in the intracellular accumulation of prostaglandins [44], raising a need for more detailed investigation of pharmacological effects in future research.…”
Section: Discussionmentioning
confidence: 94%
“…Indeed, our results provide evidence for a more intensive autophagy present in cells treated with 2. A novel study of Chi et al indicates that the downregulation of 5-Lipoxygenase via the PI3K/Akt signaling pathway results in the reduced proliferation and migration of tumor cells, confirming, once again, the importance of this enzyme in tumor treatment [43]. Nevertheless, one should have in mind that the inhibition of solely 5-LO could result in the intracellular accumulation of prostaglandins [44], raising a need for more detailed investigation of pharmacological effects in future research.…”
Section: Discussionmentioning
confidence: 94%
“…62 The PI3K–Akt signaling is activated by phosphorylation, and regulates cell proliferation, differentiation and apoptosis. 63 Activation of PI3K–Akt signaling protects cells from injury and inhibits cell apoptosis under oxidative stress, whereas inhibition of Akt activation makes cells more sensitive to oxidative stress and vulnerable to injury. 64 The PI3K–Akt signal pathway plays a vital role in several antioxidant reactions and inflammatory cascades.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that ALOX5 can promote tumour cell growth through the PI3K/AKT pathway and MAPK pathway [54,74], while GDF15 can act through the PI3/Akt pathway and TGFβ/SMAD pathway to promote tumour growth [75,76]. Therefore, in the functional study of ALOX5 and GDF15, we used the GO and KEGG databases and found by enrichment analysis that the main functions of the ALOX5 and GDF15 genes were related to lipid metabolism, the cell signalling pathway, arachidonic acid metabolism, the MAPK signalling pathway and the IL-17 signalling pathway by enrichment analysis.…”
Section: Discussionmentioning
confidence: 99%